Evolution Oriented Monitoring oriented to Security Properties for Cloud Applications - Muñoz-Gallego, Antonio Jesús (My University, 2018)
Internet is changing from an information space to a dynamic computing space. Data distribution and remotely accessible software services, dynamism, and autonomy are prime attributes. Cloud technology offers a powerful and fast growing approach to the provision of infrastructure (platform and software services) avoiding the high costs of owning, operating, and maintaining the computational infrastructures required for this purpose. Nevertheless, cloud technology still raises concerns regarding security, privacy, governance, and compliance of data and software services offered through it. Concerns are due to the difficulty to verify security properties of the different types of applications and services available through cloud technology, the uncertainty of their owners and users about the security of their services, and the applications based on them, once they are deployed and offered through a cloud. This work presents an innovative and novel evolution-oriented, cloud-specific monitoring model (including an architecture and a language) that aim at helping cloud application developers to design and monitor the behavior and functionality of their applications in a cloud environment.
Keywords: Seguridad informática; Security; Monitoring